Mitigation of acidified salmon rivers – effects of liming on young brown trout Salmo trutta. Issue 5 (14th September 2017) - Hesthagen, T.; Larsen, B. M.; Bolstad, G.; Fiske, P.; Jonsson, B.
Abstract : In southern Norway, 22 acidified rivers supporting anadromous salmonids were mitigated with lime to improve water quality and restore fish populations. In 13 of these rivers, effects on Salmo trutta and Salmo salar densities were monitored over 10–12 years, grouped into age 0 and age ≥ 1 year fish. These rivers had a mean annual discharge of between 4·9 and 85·5 m 3  s −1, and six of them were regulated for hydro‐power production. Salmo salar were lost in six of these rivers prior to liming, and highly reduced in the remaining seven rivers. Post‐liming, S. salar became re‐established in all six rivers with lost populations, and recovered in the seven other rivers. Salmo trutta occurred in all 13 study rivers prior to liming. Despite the improved water quality, both age 0 and age ≥ 1 year S. trutta densities decreased as S. salar density increased, with an average reduction of >50% after 10 years of liming. For age 0 year S. trutta this effect was less strong in rivers where S. salar were present prior to liming. In contrast, densities of S. trutta increased in unlimed streams above the anadromous stretches in two of the rivers following improved water quality due to natural recovery. Density increases of both age 0 and age ≥ 1 year S. salar showed a positive effect of river discharge. The results suggest that the decline in S. trutta density after liming is related to interspecific resource competition due to the recovery of S. salar . Thus, improved water quality through liming may not only sustain susceptible species, but can have a negative effect on species that are more tolerant prior to the treatment, such as S. trutta .